Finite Element Modelling of a Hot Roll Forging Process with Emphasis on Role of Grip - T. Jin, H.; K. Razali, M.; S. Joun, M.; H. Nam, T.; S. Kang, S. (International Journal of Engineering and Technology, 2018)
In this paper, a finite element model of grip in roll forging is presented, which has a deep influence on both finite element predictions and real process. It is considered as a tool possessing two roles, that is, force exerting role and velocity imposing role on the material. A fraction of roll separating force is exerted on the front end of the material to be pulled, which is defined by minimum value between allowable grip pulling force of the grip and roll separating force multiplied by a grip constant. Effect of the grip constant is examined, revealing that the predictions of final length and plastic deformation in major deformed region have a distinct function of the grip constant, which can be a characteristic property of the process. The approach is applied to roll forging of manufacturing a stepped bar and the predictions are compared, revealing that they are in a good agreement with each other. It is also emphasized that the new approach not only improves flexibility of adopting the difficult-to-model actual roll forging processes but it also enhances numerical stability and reliability of the finite element analysis of them.Â Â